The Effect of Person-Centered and Rational Emotive Therapy Group Counseling: A Comparative Study in Changing Self-Concept and Achievement Motivation of Low Achievement Secondary School Students in Pattani, Thailand - Sujai, Suanphiroth (2009)
The sample used for this study was limited to the low achievement students in grade 9 comprising 192 secondary school students, randomly assigned into four groups of 48: a group with the person-centered group counseling: the rational emotive group therapy; group with material and group without treatment. Each student received only one type of treatment. A total of eight sessions were attended over a four-week period by the students in the person-centered group counseling and the rational emotive group therapy. The leader of each group facilitated the 8 sessions. Each session lasted 90 minutes; the total time of meeting was 12 hours. After the treatment, all subjects were again tested by the Tennessee Self-Concept Scale and the Achievement Motivation Test. The control group was also tested simultaneously allow for a comparison to be made as to which method was the most effective. The data before and after the treatment were analyzed using t-test. The statistical procedures using the SPSS/FW program in the data analysis were the one-way analysis of variance (ANOVA). The criterion for significant difference for all analyses was set at. .05 to simplify the analysis of effectiveness for the experimental study. The findings revealed that: 1. the person-centered group counseling and the rational emotive group therapy were not significantly different in the self-concept. Within group comparison showed that the person-centered group counseling was significantly different in the scores of pretest and post test of the self-concept. 2. there was no significant difference in the mean scores of gender in the self-concept of the person-centered group counseling and the rational emotive group therapy. 3. in the person-centered group counseling and the rational emotive group therapy there were significantly different in the achievement motivation. There was significantly different in the scores of pretest and post test of the achievement motivation within group both of the person-centered group counseling and the rational emotive group therapy. 4. there was significant difference in the mean scores of gender in the achievement motivation of the person-centered group counseling and the rational emotive group therapy.